The Computer Vision For Blastocyst Segmentation - Villota Miranda, María; Ayensa-Jiménez, Jacobo; Doblaré, Manuel; Heras, Jonathan (Jornada de Jóvenes Investigadores del I3A, 2024)
In Vitro Fertilization is a technique widely used by infertile couples seeking to start a family. Deciding which embryos to implant is crucial but uncertain. In order to provide tools to help in this decision, we performed an automatic segmentation of the blastocyst using computer vision techniques, obtaining results competitive with the state of the art.